Effects of Additional Mesopores and the Surface Modification of the Y-Type Zeolite on the Alkane Oxidation Activity of Iron Complex-Encapsulated Catalysts - Takamasa Takeda; Masaya Okamura; Syuhei Yamaguchi; Hidenori Yahiro; Shiro Hikichi (Molecules)
Catalytic alkane hydroxylation activities of the iron complex encapsulated into the micropore of the Y-type zeolite and mesoporous zeolites, the latter of which were obtained by the partial removal of aluminum and alkaline treatment, have been explored by using H2O2 as the oxidant. The iron complex with tris(pyridylmethyl)amine (=TPA) encapsulated into the micropore of the genuine Y-type zeolite was a more stable and effective cyclohexane hydroxylating heterogeneous catalyst compared to the corresponding copper analogue as well as the non-encapsulated homogeneous Fe-TPA complex. The chemical modification of the zeolite supports with the organic groups led to changing the catalytic activity depending on the size and the hydrophobic or hydrophilic nature of the added organic groups. When the content of water in the solvent was increased, the activity of the hydrophilic longer chain-modified catalyst was improved compared to that applied on the reaction with the non-aqueous solvent. The hydrophobic fluoroalkyl modifier located near the entrance of the micropore hindered the access of the substrate and aqueous H2O2 to the encapsulated iron complex site in the genuine Y-type zeolite. On the other hand, the hydrophobic modification effectively improved the activity of the catalyst with the zeolite support having higher amounts of mesopores. The synergistic effect of the wider bore diameters and the hydrophobic nature derived from the fluoroalkyl chains led to the concentration of the hydrocarbon substrate near the active iron complex.